Living labs and innovation platforms: A literature review - Lie, Rico; van Paassen, Annemarie; Witteveen, Loes (WorldFish, 2023)
This literature study identifies the success and failure factors of living labs and innovation platforms. The study accomplishes this by zooming in on key characteristics and design principles of living labs and innovation platforms and distilling statements from academic and professional literature. Design principles are guidelines to follow in the design process to implement and operate a living lab or innovation platform successfully.